2016
DOI: 10.1177/1559827616629895
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Mental Health: Why Is It Relevant?

Abstract: Father's mental health is an emerging area of interest that is beginning to be recognized in research, and to a lesser extent in clinical practice and society. Fathers are part of a parenting dyad with 2 partners who are responsible for their children's emotional development. Similar to mothers, the risk for mental health problems increases once a male becomes a father, but there is limited research examining this issue. The purpose of this review is to present the available literature on father's mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 145 publications
(224 reference statements)
4
67
1
2
Order By: Relevance
“…Maternal and paternal depression are often comorbid: fathers have a heightened risk of depression when the mother is depressed (Fisher, ; Paulson & Bazemore, ). Paternal involvement may moderate the effects of maternal depression on children's emotional problems; depending on the level of paternal depressive symptoms, and on their time spent with the child, fathers can either ameliorate or cause deterioration in the child's adverse outcomes (Mezulis, Hyde, & Clark, ).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal and paternal depression are often comorbid: fathers have a heightened risk of depression when the mother is depressed (Fisher, ; Paulson & Bazemore, ). Paternal involvement may moderate the effects of maternal depression on children's emotional problems; depending on the level of paternal depressive symptoms, and on their time spent with the child, fathers can either ameliorate or cause deterioration in the child's adverse outcomes (Mezulis, Hyde, & Clark, ).…”
Section: Introductionmentioning
confidence: 99%
“…neglecting the importance of the father's mental health. However, research has shown that paternal MD are also associated with MD in their children [67]. Moreover, research has found evidence that a good paternal mental health may buffer the influence of a mother's poorer mental health on a child's behavioural and emotional problems [68].…”
Section: Plos Onementioning
confidence: 99%
“…Las investigaciones sugieren que la depresión en un miembro de la pareja se correlaciona considerablemente con la depresión en el otro. 6,7,3,8 Un estudio demostró que entre el 24 y el 50 por ciento de los hombres con PPD paterna también tenía pareja con PPD.9 Esto indica que hay una alta probabilidad de que los bebés se puedan encontrar en situaciones familiares en donde varios de los cuidadores están deprimidos, lo que puede derivar en alteraciones más graves en el desarrollo del bebé. …”
unclassified
“…Las investigaciones sugieren que la depresión en un miembro de la pareja se correlaciona considerablemente con la depresión en el otro. 6,7,3,8 Un estudio demostró que entre el 24 y el 50 por ciento de los hombres con PPD paterna también tenía pareja con PPD.…”
unclassified